Cultural Perceptions of Patient Safety among Dentists, Young Dentists and Medical Staff in Dental and Oral Hospital - Dwi Windu Kinanti Arti; Diki Bima Prasetio; Sulistyo Shanti Nur Addukha (Universitas Muhammadiyah Yogyakarta, 2020)
Patient safety culture is a major aspect of quality Dental and Oral Hospital services. There are various professions, equipment, and provide services for 24 hours without stopping. The aim is determining culture perceptions of patient safety among dentists, young dentists and medical staff in dental and oral hospitals. This type of quantitative descriptive research with cross-sectional approach. Research site in the dental and oral hospital of the University of Muhammadiyah Semarang. A sample of 65 respondents consisting of dentists, young dentists, and medical staff used simple random sampling techniques. Data analysis using univariate is presented in the frequency distribution table. The results are Perception of Dentists, Young Dentists and Medical staff, the assessment of internal cooperation, poor (50.8%), Perception the assessment of managers, good (64.4%). Perception communication appraisal of work unit, good (50.8%), Perception frequency reports of wrong actions or events is not expected, good (53.8%). The perception of the assessment of the patient safety level, good (55.4%). The perception of hospital management overall assessment, poor (58.5%). The conclusion is the culture of patient safety in the Dental and Oral Hospital from the perception of Dentists and Medical Staff are good, but the perception of Young Dentists is still poor.